Co-gasification of coal and empty fruit bunch in an entrained flow gasifier : A process simulation study - Mohd Rizauddin, Deraman; Ruwaida, Abdul Rasid; Mohamad Rizza, Othman; Suli, L. N. M. (IOP Publishing Ltd, 2019)
Co-gasification of coal and biomass is a proven method to improve gasification performance and a platform towards being independent of fossil fuel in power generation. Thus, this research was conducted to assess the feasibility of coal and EFB as fuels in co-gasification using Aspen HYSYS. A sequential model of an EFG was developed to predict the syngas composition and the optimum operating condition of the gasifier. The process was modelled with a set of five reactors to simulate various reaction zones of EFG in accordance with its hydrodynamics. The model considers devolatilization, char and volatile combustion, char gasification and water-gas shift reactions. The model prediction has exhibited excellent agreement with the experimental results. Three parameters of BR, Top and S/F were considered to account for their impacts on syngas composition in the process. The CE, CGE, PE and HHV were adopted as the indicators of process performance. The optimal values of BR, Top and S/F were 50%, 950°C and 0.75, respectively. While the value of CE reached above 90% and the maximum value of CGE, PE and HHV was obtained. This finding should be helpful in designing, operating, optimizing and controlling any co-gasification process especially in the entrained flow system.